3D NUMERICAL HYDRODYNAMICAL MODELS OF THE PRECESSING THICK ACCRETION DISK AND ON- AND OFF-STATE GENERATIONS IN MICROQUASARS - Nazarenko, V. V.; Nazarenko, S. V. (Одеські астрономічні публікації, 2017)
The thick accretion disk and donor’s wind on the example of CYG X-1 are computed. The main aim of the present simulations is to calculate the precessing thick accretion disk and ON- and OFF-state generation by the methods of 3D numerical hydrodynamics. The main task of the present research is to investigate the dependencies of the central disk temperature and mass accretion rate versus time. Non-stationary Euler’s hydrodynamical equations are resolved by astrophysical variant of large-particle method by Belotserkovskii & Davydov. The ON- and OFF-state generation for the precessing thick accretion disk was setting. The correlation between radio ﬂux and X-ray was setting. Our present calculations also show that in the cases of the thick accretion disk the jet velocities will be close to 0.24 -0.26 of light speed (see for instance SS433) and on contrary in the cases of a thin accretion disk jet velocities will be close to 0.98 -0.99 of light speed (see for instance CYG X-1).